2021
DOI: 10.1111/1365-2656.13447
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling temporal food web dynamics facilitates understanding of ecosystem functioning

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 61 publications
7
66
1
2
Order By: Relevance
“…Experimental evidence supports findings that climate change can and will drive changes in the pelagic primary production (Sommer et al, 2012), and a thorough review illustrating benthic-pelagic coupling shows ecosystem-wide consequences of altered pelagic primary production (Griffiths et al, 2017), probably also impacting food web dynamics (Kortsch et al, 2021).…”
Section: Phytoplankton and Cyanobacteriasupporting
confidence: 53%
See 2 more Smart Citations
“…Experimental evidence supports findings that climate change can and will drive changes in the pelagic primary production (Sommer et al, 2012), and a thorough review illustrating benthic-pelagic coupling shows ecosystem-wide consequences of altered pelagic primary production (Griffiths et al, 2017), probably also impacting food web dynamics (Kortsch et al, 2021).…”
Section: Phytoplankton and Cyanobacteriasupporting
confidence: 53%
“…The consequences of climate change are difficult to predict, also because research into the longterm dynamics of food webs is still scarce (Kortsch et al, 2021;Pecuchet et al, 2020;Törnroos et al, 2019). Some common patterns arise from the wealth of recent studies, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the data do not reveal information about feeding rates or biomasses. Despite this, metabarcoding has the potential to serve as an important complement to food web models that implement population biomasses and metabolic energy demands [ 67 ], by bringing details of species-specific feeding interactions to the model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that marine copepod species have declined in abundance since the 1980s, while euryhaline or limnetic, often small species have increased (Hänninen et al, 2015;Suikkanen et al, 2013;Kortsch et al, 2021). The observed decline of marine taxa has been linked to the reduction in surface-water salinity since the 1980s (Vuorinen et al, 2015), whereas the increase of brackish-water taxa has been positively influenced by the temperature increase, directly or indirectly (Mäkinen et al, 2017).…”
Section: Zooplanktonmentioning
confidence: 96%